(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The horrific incidents in Aurora, Colorado, and Newtown, Connecticut have reignited societalperceptions of mentally ill people as dangerous and criminals. Unfortunately, rather than research,this perception is founded on speculation and fear. The empirical studies on mental illness and criminalconduct is reviewed in the following article. This literature reveals three important trends. First, comparedto the general population, the frequency of mental illness is significantly greater among those who havehad experience with the criminal justice system. Second, people with psychotic and externalisingbehavioural disorders, especially those who abuse drugs and alcohol, are more likely to commit acts ofviolence than people with other types of mental illness. Third, mental illness is one of severalcriminogenic risk variables that interact in complicated ways to influence individual behaviour.